Oncolytic Viruses as Anticancer Vaccines - Woller, Norman; Gürlevik, Engin; Ureche, Cristina-Ileana; Schumacher, Anja; Kühnel, Florian (Frontiers in Oncology, 2014)
Oncolytic virotherapy has shown impressive results in preclinical studies and first promising therapeutic outcomes in clinical trials as well. Since viruses are known for a long time as excellent vaccination agents, oncolytic viruses are now designed as novel anticancer agents combining the aspect of lysis-dependent cytoreductive activity with concomitant induction of antitumoral immune responses. Antitumoral immune activation by oncolytic virus infection of tumor tissue comprises both, immediate effects of innate immunity and also adaptive responses for long lasting antitumoral activity which is regarded as the most prominent challenge in clinical oncology. To date, the complex effects of a viral tumor infection on the tumor microenvironment and the consequences for the tumor-infiltrating immune cell compartment are poorly understood. However, there is more and more evidence that a tumor infection by an oncolytic virus opens up a number of options for further immunomodulating interventions such as systemic chemotherapy, generic immunostimulating strategies, dendritic cell-based vaccines, and antigenic libraries to further support clinical efficacy of oncolytic virotherapy.